Economic psychology of the Veblen goods: an empirical study of the preferences of clients of luxury car dealerships in the Chicagoland area - Ptak Krzysztof (My University, 2007)
The purpose of the thesis is to determine if a theory of Thorstein Veblen is accurate by doing research and to find out the customer’s preferences for luxury automobiles. His theory suggests that as price increases people will want the product even more. The author developed a survey to obtain data for some statistical analysis. The results showed what customers thought of the luxury cars and how they responded to several characteristics: there were significant correlations in the consumers’ preferences, e.g. with respect to the country of origin of the car (e.g. customers who had preference for French cars also tended to prefer Korean cars, when they had a preference for Swedish cars they also tended to prefer British cars, and when they had a preference for British cars they also tended to prefer American cars). Analysis also revealed that such characteristics as plush interior and speed correlate positively with the image of a exclusive luxury car, while other features (such as expensive, superior driving characteristics, extremely comfortable, or high status) do not. The results showed that Veblen’s theory is not accurate in today’s time, but also some of the results may be random due to improperly stated questions.
Psychologia ekonomiczna i teoria Veblena: badania empiryczne preferencji klientów salonów luksusowych samochodów w rejonie Chicago, USA
Keywords: management; luxury automobiles; Thorstein Veblen's theory; economic psychology; consumer's preferences